Thermal Analysis of Switched Reluctance Motor Based on RMXprt/Motor-CAD - bardan, Hussein; Ali, Amer (Anbar Journal of Engineering Sciences, 2023)
Switched reluctance motor (SRM) is an electric motor works based on the reluctance torque produced due to the variation of the rotor pole position with respect to stator poles. This paper adopts a thermal analysis on a 4-phase, 8/6 pole, 550W, SRM. Lumped parameters thermal network method(LPTN) is used in this analysis based on a combination of RMXprt/Motor-CAD software, in two- dimensional(2D), steady-state, with different cooling methods, and with different loading conditions. Motor losses like core losses, copper losses, and mechanical losses are regarded as the heat sources in SRM which are calculated by RMXprt software. The thermal analysis achieved by Motor-CAD includes displaying the temperature distribution on different motor parts like stator winding, stator poles, stator yoke, rotor poles, rotor yoke, shaft, covers, and housing. The analysis results showed the increasing temperature distribution on different motor parts with increasing motor loading conditions. Also, this temperature distribution is recorded using three different cooling methods. The comprehensive thermal analysis applied in this work will assist the motor designer in choosing a better motor thermal design without needing to produce and test costly prototype motors.